Presence of Histopathological Treatment Effects at Resection of Recurrent Glioblastoma: Incidence and Effect on Outcome. Issue 6 (16th November 2018) - Dalle Ore, Cecilia L; Chandra, Ankush; Rick, Jonathan; Lau, Darryl; Shahin, Maryam; Nguyen, Alan T; McDermott, Michael; Berger, Mitchel S; Aghi, Manish K
Abstract: BACKGROUND: Resection may be appropriate for select patients with recurrent glioblastoma. The incidence of histopathological findings related to prior treatment and their prognostic implications are incompletely characterized. OBJECTIVE: To quantify the incidence and survival outcomes associated with treatment effect at resection of recurrent glioblastoma (GBM). METHODS: Patients who underwent resection for recurrent GBM were retrospectively reviewed, and pathology, treatment history, and survival data were collected. Treatment effect was defined as any component of treatment-related changes on pathology. RESULTS: In total, 110 patients underwent 146 reoperations. Median age at first reoperation was 57.2 yr and overall survival from reoperation was 10.8 mo. Treatment effect of any kind was noted in 81 of 146 reoperations (55%). Increased treatment effect was observed closer to radiotherapy; by quartile of time from radiotherapy, the rates of treatment effect were 77.8%, 55.6%, 40.7%, and 44.4% ( P = .028). Treatment effect was associated with earlier reoperation (8.9 vs 13.8 mo after radiotherapy, P = .003), and the presence of treatment effect did not impact survival from primary surgery (25.4 vs 24.3 mo, P = .084). Patients treated with bevacizumab prior to reoperation were less likely to have treatment effect (20% vs 65%, P < .001). CONCLUSION: Histopathological treatment-related changes are evident in a majority of patients undergoing resection for recurrent glioblastoma. There was no association of treatment effect with overall survival from primary surgery.